Increasing Achievement in Science Learning About Various Types of Objects Through Experimental Methods in Class IV Students of SDN Pondok Kacang Timur 03 Semester 1 Year 2015/2016 - Sutinah Sutinah (Eduvest - Journal of Universal Studies, 2021)
In essence, teaching and learning activities are a process of interaction or reciprocity between teachers and students in the learning unit. Improving science learning achievement about various forms of objects in fourth grade students at SD Negeri Pondok Kacang Timur 03 Semester 1 of 2015/2016 through the experimental method. This research uses Classroom Action Research (CAR). Based on the results of the discussion of data analysis that has been carried out in cycle I and cycle II in this study, it can be concluded as follows: The use of experimental methods can improve student learning outcomes in science subjects subject to various forms of objects in class IV semester I SDN Negeri Pondok Kacang Timur 03 academic year 2015/2016, this is indicated by an increase in learning outcomes, namely the learning process before the action shows low learning outcomes, namely students whose scores meet the KKM as many as 13 students or 37%, students who have not completed 21 students or 61% with the highest score of 90 and the lowest score was 40. In the first cycle the number of students who completed 21 students or 61% while those who had not completed 13 students or 39%. The minimum score is 50 and the maximum value is 90. In the second cycle there was an increase in learning outcomes, namely the number of students' completeness was 32 students or 94%. The minimum score is 70 and the maximum value is 100. There is an increase in the average score, namely 65 in the pre-cycle to 73 in the first cycle and increasing to 85 in the second cycle. Thus it can be concluded that using the experimental method can improve student learning outcomes in science subjects on the subject of various forms of objects in class IV semester I SDN Negeri Pondok Kacang Timur 03 academic year 2015/2016 can improve learning outcomes.